2022
DOI: 10.1101/2022.03.22.22272775
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk of death following SARS-CoV-2 infection or COVID-19 vaccination in young people in England: a self-controlled case series study

Abstract: Objectives: To assess whether there is a change in the incidence of cardiac and all-cause death in young people following COVID-19 vaccination or SARS-CoV-2 infection in unvaccinated individuals. Design: Self-controlled case series. Setting: National, linked electronic health record data in England. Study population: Individuals aged 12-29 who had received at least one dose of COVID-19 vaccination and died between 8 December 2020 and 2 February 2022 and registered by 16 February 2022 within 12 weeks of CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…A Hungarian study also found a decreased risk of (all-cause) mortality after vaccination (Pálinkás, A., & Sándor, J., 2022). Two other studies, from the United Kingdom and the United States, did not find evidence for an increased risk of mortality after vaccination (Xu et al, 2021;Nafilyan et al, 2022). This is consistent with our results, where, on a population level, we found no indication of an increased mortality risk following vaccination.…”
Section: Discussionsupporting
confidence: 92%
“…A Hungarian study also found a decreased risk of (all-cause) mortality after vaccination (Pálinkás, A., & Sándor, J., 2022). Two other studies, from the United Kingdom and the United States, did not find evidence for an increased risk of mortality after vaccination (Xu et al, 2021;Nafilyan et al, 2022). This is consistent with our results, where, on a population level, we found no indication of an increased mortality risk following vaccination.…”
Section: Discussionsupporting
confidence: 92%
“…Table 1. The ratios of death from the diseases of the circulatory system [11]. The excess mortality in the age group 0-14 started to increase significantly after the second half of 2021 and the graph in Figure 1.…”
Section: *Presenting and Corresponding Authormentioning
confidence: 92%
“…We have communicated that from our medical standpoint the risks of not being vaccinated outweigh the risks of vaccination. An unvaccinated young person has an increased risk of experiencing a more severe illness and of developing long COVID, with gaps in knowledge about long-term outcome [18][19][20][21][22][23][24]. We have also pointed the family to available information resources [25].…”
Section: Introductionmentioning
confidence: 99%